دور خطبة الجمعة في تعزيز قيم التواصل الاجتماعي لدى الشباب دراسة ميدانية - كهمان, الرميصاء (University of eloued جامعة الوادي, 2016)
تناكلت الدراسة موضوع " دور خطبة الجمعة في تعزيز قيم التواصل الاجتماعي لدى الشباب دراسة ميدانية " على عينة من شباب كلاية الوادم بهدؼ الإجابة عن التساؤلات ابؼطركحة للوصوؿ إلذ أىداؼ كنتائج بؿققة في دكر خطبة ابعمعة في تعزيز قيم التواصل الاجتماعي لدل الشباب. كقد شملت ىذه الدراسة مقدمة كأربعة فصوؿ، بيثل الفصل الأكؿ الإطار ابؼنهجي للدراسة حيث اشتمل على إشكالية الدراسة كأسباب اختيار ابؼوضوع، كأبنية كأىداؼ الدراسة، كمصطلحات الدراسة كالدراسات السابقة، كالإجراءات ابؼنهجية للدراسة. أما الفصل الثاني: قيم التواصل الاجتماعي الشبابية، كيشمل مبحثتُ: ابؼبحث الأكؿ القيم الأسرية كابؼبحث الثاني القيم الأخلاقية. أما الفصل الثالث بعنواف مقومات خطبة ابعمعة كدكرىا في التواصل الاجتماعي، ك ق س م الذ مبحثتُ: ابؼبحث الأكؿ: مقومات خطبة ابعمعة، كابؼبحث الثاني: دكر خطبة ابعمعة في التواصل الاجتماعي. كفي الفصل الرابع كالأختَ ابعانب ابؼيداني حيث عرض النتائج كبرليلها كمناقشتها، كختمت ىذه الدراسة بنتائج كتوصيات. This survey is dealing with the role of Friday speech in supporting the values of the social communication among young people aprachcal survey among the gouth of el-oued in order to answer the raised question to achieve the objectives and the results to the role of Friday speach. This survey consists of an introduction and four chapters represents the methodological frame work of the survey. It consists of the problematie, the reasons behind choosing the topie, the significance and objectives of the survey, lcey terns, literatune revieur, and the methodological procedures of the survey. The second chapter: the values of (social communication) among gouth it involves tow sections the first section, the family values and the second sectionthe moral values, the third chapter is entitled the underpping of the Friday speach and its role of the social communication it consists of time sections: the first section is the underpping of the Friday speech and the second section is is the role of the Friday speach in the social communication. In the last chapter, the practical part presents, analyses and discuses the results, finally we conclude his survey with a presenting results and recomondations.
ماستر دعوة
Keywords: قيم التواصل الاجتماعي,خطبة الجمعة,الشباب; The values of social communication, Friday sermon, young people